The Initial Step for Developing Sustainable Urban Drainage System in Semarang City-Indonesia. (2017) - Suripin; Pujiastuti, Ratih; Widjonarko
Abstract: The objective of this study is to evaluate the impacts of the climate changes, land subsidence, and land use changes to flood in East Semarang Drainage System. Rainfall data from three stations in the period of 1990-2014 were used to describe the changes of rainfall characteristics, while sea level rise was analyzed based on sea level data in the period 1985-2008, combined with land subsidence data. The trend of rainfall characteristics changes were analyzed by statistical regression. HEC-MHS and HEC-RAS were used to estimate flood hydrograph and flood level. The results showed that during the last three decades, the annual rainfall and maximum daily rainfall is likely to increase by 22.64 mm/year and 2.56 mm/year consecutively, while the number of rainy days tends to decrease by 4 days/year. The rate of land subsidence is 5.34 cm/year, and SLR of 2.3 mm/year. Flooding and tidal inundation due to increasing rainfall and sea level rise is predicted to increase by 4.65% for a period of 17 years. Changes in rainfall characteristics contribute to increasing flooded area of 3.61%, while the SLR of 1.04%. Land subsidence is predicted to lead to an increase in flooding and tidal inundation by 23.59%. These three factors together combined with land use changes would increase the flood inundation of 26.69% for the period 2014 through 2031.